BUSINESS MODELS AS A STRATEGY IN BUSINESS CRISIS ON ONLINE FOOD SERVICES - Fernando, Rochelle (International Interdisciplinary Conference on Sustainable Development Goals, 2023)
Significant modifications occur during business crises. Considering the COVID-19 pandemic, the established business models need to be reevaluated, requiring a driving force for industry transformation. The purpose of this paper is to assess the business models used by online food services for delivery. Likewise, the methodology enforces survey-descriptive quantitative research, addressing the general problem, descriptive research hypotheses and research instruments, categorizing as open-ended questions, performing its construction and validity checks by experts and statisticians, checking the reliability of the instrument used, and performing descriptive statistical analysis. In terms of data collection, it resorts to secondary data; the survey method was done face-to-face. For data analysis, the sample size and populations in the study were the selected 100 online food businesses in Balanga City, with or without physical stores, and in management positions, with consent on data gathering from the Municipality of Balanga-City License, Permit, and Franchising Office. Moreover, the conclusion of the study is expected to provide useful insights into the current issues by online food businesses, enabling them to stay competitive in the marketplace. The inputs will serve as a vital resource for online food businesses. The implications of this study, particularly for small and medium-sized firms (SMEs), are helpful as a point of reference for maintaining business. In place of the study's recommendation, it focuses on the structure of online business models for delivery and offers suggestions for online food business undertakings. Keywords: business crises, online food delivery services, business models, online food business, Small and Medium-Sized (SMEs)